2003
DOI: 10.1002/chin.200322184
|View full text |Cite
|
Sign up to set email alerts
|

High‐Yield, One‐Pot Syntheses of Symmetrical Diaryl‐N,N‐dialkyl Carbamoylmethylphosphine Oxide (CMPO) Ligands.

Abstract: Organo-phosphorus compoundsOrgano-phosphorus compounds S 0080 High-Yield, One-Pot Syntheses of Symmetrical Diaryl-N,N-dialkyl Carbamoylmethylphosphine Oxide (CMPO) Ligands. -A simple one-pot process is reported for the synthesis of title compounds (III) useful as actinoid extractants. -(GUILLORY, P.; KAPOOR, R. N.; PANNELL*, K. H.; SCHULTE, L.; MCKEE, S. D.; ZHANG, Z.-Y.; BARTSCH, R. C.; Synth. Commun. 33 (2003) 2, 325-330; Dep. Chem., Univ. Tex., El Paso, TX 79968, USA; Eng.) -H. Haber 22-184

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Ligand Synthesis and Characterization. The synthesis of ligand A was recently reported 75 as was its structure, along with those of the uranyl and some organotin chloride complexes. 76 The presence of the potentially reactive P(O)-CH 2 -C(O) methylene group suggests that a series of derivatives could be forthcoming via substitutions at this position.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ligand Synthesis and Characterization. The synthesis of ligand A was recently reported 75 as was its structure, along with those of the uranyl and some organotin chloride complexes. 76 The presence of the potentially reactive P(O)-CH 2 -C(O) methylene group suggests that a series of derivatives could be forthcoming via substitutions at this position.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the Paine group reported that treatment of R 2 P(O)CH 2 C(O)NEt 2 (R ) EtO, Ph) with NaH followed by addition of substituted benzyl chlorides 77 ligands. [75][76][77][78] Because of the asymmetric center at the PCH atom, many of the NMR signals are doubled, as noted above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation